La expresión corporal para potenciar la creatividad en las niñas y niños de 3 a 5 años del centro de educación inicial My Little Friends en la ciudad de Loja. Periodo 2014-2015 - Vidal Barrera, Glenda Natalia (2016)
This research work called body language to enhance creativity in children from 3 to 5 years Early Childhood Education Center My Little Friends of the City of Loja. 2014-2015 period, had as its overall objective to contribute to this research on body language to enhance creativity. For the development of this work the following methods were used: scientific, inductive deductive, analytical synthetic, descriptive statistics, the techniques used were the survey of teachers, and instruments test and re-test of the Portage Guide applied to 32 children from 3 to 5 years and 3 teachers, a statistical analysis was performed and was obtained as a result 100% of the teachers said that body language if affects the development of creativity of children, in re -test applied to children the following percentages 76.92% of children meets the coloring inside the figures obtained, the 69.23% in clay molds clay objects. Finally it was concluded that activities implemented helped foster creativity in children from 3 to 5 years Early Childhood Education Center My Little Friends.